2015
DOI: 10.1371/journal.pone.0140020
|View full text |Cite
|
Sign up to set email alerts
|

Downhill Running-Based Overtraining Protocol Improves Hepatic Insulin Signaling Pathway without Concomitant Decrease of Inflammatory Proteins

Abstract: The purpose of this study was to verify the effects of overtraining (OT) on insulin, inflammatory and gluconeogenesis signaling pathways in the livers of mice. Rodents were divided into control (CT), overtrained by downhill running (OTR/down), overtrained by uphill running (OTR/up) and overtrained by running without inclination (OTR). Rotarod, incremental load, exhaustive and grip force tests were used to evaluate performance. Thirty-six hours after a grip force test, the livers were extracted for subsequent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
63
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(81 citation statements)
references
References 41 publications
(78 reference statements)
10
63
0
8
Order By: Relevance
“…Taken together, these results indicated that APPL1 could be part of the molecular mechanism that contributes to the glucose homeostasis in the liver of overtrained mice. Da Rocha et al 3 using the same liver samples of the current investigation verified that mice from the OTR/down group improved some initial proteins of the hepatic insulin signaling pathway, but upregulated the TRB3 and its association with Akt, implying a limitation on this downstream point of the insulin signaling pathway. The authors also observed high levels of hepatic glycogen 3 , which leads to the hypothesis that another molecule could be responsible for this result especially in the OTR/down and OTR/up groups.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Taken together, these results indicated that APPL1 could be part of the molecular mechanism that contributes to the glucose homeostasis in the liver of overtrained mice. Da Rocha et al 3 using the same liver samples of the current investigation verified that mice from the OTR/down group improved some initial proteins of the hepatic insulin signaling pathway, but upregulated the TRB3 and its association with Akt, implying a limitation on this downstream point of the insulin signaling pathway. The authors also observed high levels of hepatic glycogen 3 , which leads to the hypothesis that another molecule could be responsible for this result especially in the OTR/down and OTR/up groups.…”
Section: Discussionsupporting
confidence: 68%
“…Although the other two OT protocols performed in uphill and without inclination led to similar decrements in the analyzed performance parameters 3,12,13 , they induced particular modulations of the hepatic insulin signaling pathway 3 . Thus, we also evaluated their effects on the hepatic protein levels of APPL1 and APPL2.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations